Comparative Analysis of Outer Membrane Vesicle Isolation Methods With an Escherichia coli tolA Mutant Reveals a Hypervesiculating Phenotype With Outer-Inner Membrane Vesicle Content - Reimer, Shelby L.; Beniac, Daniel R.; Hiebert, Shannon L.; Booth, Timothy F.; Chong, Patrick M.; Westmacott, Garrett R.; Zhanel, George G.; Bay, Denice C. (Frontiers in Microbiology, 2021)
Outer membrane vesicles (OMVs) produced by Gram-negative bacteria are mediators of cell survival and pathogenesis by facilitating virulence factor dissemination and resistance to antimicrobials. Studies of OMV properties often focus on hypervesiculating Escherichia coli mutants that have increased OMV production when compared to their corresponding wild-type (WT) strains. Currently, two conventional techniques, ultracentrifugation (UC) and ultradiafiltration (UF), are used interchangeably to isolate OMVs, however, there is concern that each technique may inadvertently alter the properties of isolated OMVs during study. To address this concern, we compared two OMV isolation methods, UC and UF, with respect to final OMV quantities, size distributions, and morphologies using a hypervesiculating Escherichia coli K-12 ∆tolA mutant. Nanoparticle tracking analysis (NTA) indicated that UC techniques result in lower vesicle yields compared to UF. However, UF permitted isolation of OMVs with smaller average sizes than UC, highlighting a potential OMV isolation size bias by each technique. Cryo-transmission electron microscopy (cryo-TEM) visualization of isolated OMVs revealed distinct morphological differences between wild-type and ∆tolA OMVs, where ∆tolA OMVs isolated by either UC or UF method possessed a greater proportion of OMVs with two or more membranes. Proteomic OMV analysis of WT and ∆tolA OMVs confirmed that ∆tolA enhances inner plasma membrane carryover in multi-lamellar OMVs. This study demonstrates that UC and UF are useful techniques for OMV isolation, where UF may be preferable due to faster isolation, higher OMV yields and enrichment of smaller sized vesicles.